WALKA PARTYZANCKA Z „MONARCHO-FASZYSTOWSKIM REŻIMEM” W FILMOWEJ INTERPRETACJI OKRESU BRL-U - Jóźwiak, Wojciech (Przegląd Wschodnioeuropejski, 2024)
The politically pressured narrative of the partisan fights from June 1941 to September 1944 became one of the ideological foundations of the Bulgarian People’s Republic. Creating and consolidating the imposed picture of events was an extremely one-sided and manipulated interpretation of the civil war in Bulgaria in the first half of the 1940s. Its film and literary performance contributed significantly to the creation of a barrier, described by Pierre Sorlin, separating the recipients (viewers/readers) seduced by a one-sided narrative from the historical truth.